2016
DOI: 10.1371/journal.pntd.0004969
|View full text |Cite
|
Sign up to set email alerts
|

The Ectodomain of Glycoprotein from the Candid#1 Vaccine Strain of Junin Virus Rendered Machupo Virus Partially Attenuated in Mice Lacking IFN-αβ/γ Receptor

Abstract: Machupo virus (MACV), a New World arenavirus, is the etiological agent of Bolivian hemorrhagic fever (BHF). Junin virus (JUNV), a close relative, causes Argentine hemorrhagic fever (AHF). Previously, we reported that a recombinant, chimeric MACV (rMACV/Cd#1-GPC) expressing glycoprotein from the Candid#1 (Cd#1) vaccine strain of JUNV is completely attenuated in a murine model and protects animals from lethal challenge with MACV. A rMACV with a single F438I substitution in the transmembrane domain (TMD) of GPC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…However, substitution F438I or F427I in GPC TMD alone was not able to completely attenuate the virulence of the viruses in vivo [ 31 , 34 ]. We previously reported that replacement of the ectodomain of MACV GPC with that of Cd#1-GPC (MCg1) also attenuated MACV, suggesting that the ectodomain of Cd#1 contains additional attenuation factors [ 37 ]. In this study, we found that the MCg1 chimeric virus frequently underwent mutations in animals to gain two glycans corresponding to the N83 and N166 glycosylation sites in MACV GPC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, substitution F438I or F427I in GPC TMD alone was not able to completely attenuate the virulence of the viruses in vivo [ 31 , 34 ]. We previously reported that replacement of the ectodomain of MACV GPC with that of Cd#1-GPC (MCg1) also attenuated MACV, suggesting that the ectodomain of Cd#1 contains additional attenuation factors [ 37 ]. In this study, we found that the MCg1 chimeric virus frequently underwent mutations in animals to gain two glycans corresponding to the N83 and N166 glycosylation sites in MACV GPC.…”
Section: Discussionmentioning
confidence: 99%
“…Later, 100% of the MCg1-infected mice contained a population of GPC A168S/T after 42 days of infection ( S2 Table ). Mutations were not observed after five serial passages of MCg1 in vitro [ 37 ] and did not affect MCg1 growth in vitro , which is important for development of a genetically stable and attenuated vaccine candidates [ 30 ]. No mutations occurred in MCg1 in cell culture experiments in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1959 the Bolivian hemorrhagic fever was clinically recognized in the provinces of Mamoré, Itenez, Tratamiento. Aunque la infección por arenavirus es una enfermedad potencialmente mortal, la mayor parte de los pacientes presentan un cuadro de gravedad moderada, que necesita solamente adecuada hidratación y antipiréticos y antiinflamatorios (17,35,36). La atención de los pacientes con signos de severos debe tener un manejo agresivo.…”
Section: Arenavirus In South Americaunclassified
“…Even though the arenavirus infection is a potentially deadly disease, most of the patient present a moderate severity condition, that only needs proper hydration antipyretics and anti-inflammatories (17,35,36). The care of patients with severe signs must include some aggressive management.…”
Section: Treatmentmentioning
confidence: 99%